2001
DOI: 10.1091/mbc.12.9.2894
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian Dynamin-like Protein DLP1 Tubulates Membranes

Abstract: Dynamins are large GTPases with mechanochemical properties that are known to constrict and tubulate membranes. A recently identified mammalian dynamin-like protein (DLP1) is essential for the proper cellular distribution of mitochondria and the endoplasmic reticulum in cultured cells. In this study, we investigated the ability of DLP1 to remodel membranes similar to conventional dynamin. We found that the expression of a GTPase-defective mutant, DLP1-K38A, in cultured cells led to the formation of large cytopl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
260
0
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 268 publications
(279 citation statements)
references
References 35 publications
18
260
0
1
Order By: Relevance
“…Although it is unclear why we have not observed similar Dnm1p rings/collars in vitro, one possibility is that one or more components of the Dnm1p-mediated fission machinery (e.g., Mdv1p and/or Fis1p) are required for the formation of functional, higher order Dnm1p structures (Mozdy et al, 2000;Tieu and Nunnari, 2000). Based on the observation that the Dnm1p homolog DRP1/DLP1 can form oligomers (Yoon et al, 2001), and our in vivo evidence that Dnm1p is required for mitochondrial fission, we think it is likely that Dnm1p also forms rings or collars around mitochondrial tubules at sites where constriction and fission will occur.…”
Section: Dnm1p Is a Functional Gtpasementioning
confidence: 92%
See 1 more Smart Citation
“…Although it is unclear why we have not observed similar Dnm1p rings/collars in vitro, one possibility is that one or more components of the Dnm1p-mediated fission machinery (e.g., Mdv1p and/or Fis1p) are required for the formation of functional, higher order Dnm1p structures (Mozdy et al, 2000;Tieu and Nunnari, 2000). Based on the observation that the Dnm1p homolog DRP1/DLP1 can form oligomers (Yoon et al, 2001), and our in vivo evidence that Dnm1p is required for mitochondrial fission, we think it is likely that Dnm1p also forms rings or collars around mitochondrial tubules at sites where constriction and fission will occur.…”
Section: Dnm1p Is a Functional Gtpasementioning
confidence: 92%
“…Recently, the Caenorhabditis elegans (DRP-1) (Labrousse et al, 1999) and mammalian (DRP1/DLP1/DVLP) homologs of yeast Dnm1p were also shown to be required for mitochondrial fission in vivo (Smirnova et al, 2001). Bacterially expressed mammalian DRP1/DLP1 appeared to form stacked rings/collars that tubulated and constricted tubules composed of synthetic lipids (Yoon et al, 2001). Although it is unclear why we have not observed similar Dnm1p rings/collars in vitro, one possibility is that one or more components of the Dnm1p-mediated fission machinery (e.g., Mdv1p and/or Fis1p) are required for the formation of functional, higher order Dnm1p structures (Mozdy et al, 2000;Tieu and Nunnari, 2000).…”
Section: Dnm1p Is a Functional Gtpasementioning
confidence: 99%
“…Although Dnm1p is related to dynamin, there is currently no ultrastructural evidence that this yeast protein assembles into higher-order structures. However, two recent studies showed that mammalian Drp1 (also called Dlp1) [26,29] assembles to form rings in vitro.…”
Section: Fission and The Outer Membrane Gtpase Dnm1pmentioning
confidence: 99%
“…This ring formation induces tubulation of synthetic liposomes, raising the possibility that the mitochondrial dynamin family members form rings around mitochondrial membranes in vivo before organelle fission [29]. Clearly, more efforts must be made to determine whether Dnm1p forms rings and whether the rings formed in vitro are functionally and structurally equivalent to the punctate structures that regulate mitochondrial fission in vivo.…”
Section: Fission and The Outer Membrane Gtpase Dnm1pmentioning
confidence: 99%
“…This suggests that all dynamin-related fission molecules may function by a common mechanism (Praefcke and McMahon, 2004). Mammalian Drp-1 has also been shown to form tubules (Yoon et al, 2001), but other molecules are required to organize and constrict mitochondria after formation of Drp-1 tubules. In particular, knocking down endophilin B1, a member of a family of proteins involved in endocytic vesicle formation, promotes the formation of Drp-1 tubules that elongate through the cytoplasm without breaking down the mitochondrial network (Karbowski et al, 2004b).…”
Section: Fissionmentioning
confidence: 99%